Student’s Junior High School Mathematical Connection Ability Based On The Big Five Personality - Aulia Suci Wardina; Nurjanah Nurjanah; Eyus Sudihartinih (JME (Journal of Mathematics Education), 2021)
Each individual has a diverse personality which is categorized by the Big Five Personality traits and it’s important for a successful education. A successful education especially in mathematics major aimed at the good of student’s mathematical abilities, one of which is good mathematical connection ability.  This research aims to determine the mathematical connection ability of junior high school students based on the Big Five personality in Bekasi. This research used qualitative research case studies with data triangulation. Participants of this research were junior high school students in grade ninth. The instrument used in the form is a test description as many as four questions that refer to the indicators of mathematical connection ability and has been consulted with experts and the Big Five personality traits questionnaire that has been adopted. The results of this research describe: 1) mathematical connection ability of the student in Extraversion dimension on indicator 1 was 60%,  indicator 2 was 0%, and indicator 3 was 0%, 2) the mathematical connection ability of students in Agreeableness dimension on indicator 1 was 60%,  indicator 2 was 25%, and indicator 3 was 25%, 3) mathematical connection ability of students in Conscientiousness dimension on indicator 1 was 60%,  indicator 2 was 35%, and indicator 3 was 25%, 4) mathematical connection ability of a student in Neuroticism dimension on indicator 1 was 20%,  indicator 2 was 0%, and indicator 3 was 20%, 5) mathematical connection ability of students in Openness dimension on indicator 1 was 64.21%,  indicator 2 was 27.37%, and indicator 3 was 34.21%.